Radiation characteristics of a flexible micro-electro-mechanical system antenna on a liquid crystal polymer substrate. (November 2015) - Lin, C.; Lixin, X.; Qi, H.
Abstract : Liquid crystal polymers are flexible polymer materials that can be used as a substrate in flexible micro-electro-mechanical system antennas. Flexible liquid crystal polymer substrate antennae can satisfy the demand for wearable and conformal applications. In this study, a flexible micro-electro-mechanical system antenna based on a liquid crystal polymer substrate is presented with a central frequency of 14 GHz. The relationships between the electrical parameters and the curvature K are obtained in order to investigate the radiation characteristics of the bent antenna with 0.04 ≤ K ≤ 0.2. The analysis results show that the antenna with a liquid crystal polymer substrate demonstrates a good radiation performance in its bent state with 0.04 ≤ K ≤ 0.2, which provides a viable option for wearable and conformal applications.